Central giant cell granuloma: a case report - Butel Antoine; Di Bernardo Gemma; Louvet Beatrice (EDP Sciences, 2018)
Introduction: Central giant cell granuloma (CGCG) is an uncommon benign bony lesion that occurs in the mandible and maxilla. Observation: A 30-year-old woman was evaluated for a radiolucent lesion of the mandible, which was discovered by chance. This image was associated with a painless swelling covered by normal mucosa. No symptoms were associated. After surgical excision, histological examination of the surgical specimen concluded a CGCG. Surgical follow-up was simple, and the first radiological test performed 3 months after confirming the onset of bone healing. Comments: The clinical behavior of CGCG ranges from a slow-growing asymptomatic swelling to an aggressive lesion with pain, local osteolysis, root resorption and tooth displacement. Therapeutic options have greatly varied in recent years. Nonsurgical treatments with alpha-interferon, calcitonin, and corticosteroids have been described and their benefits may be worthy of consideration. Conclusion: A surgical approach is considered as the traditional treatment and is still the most accepted one. However, in some publications, authors disagree on the type of surgery that should be performed.